Savoirs et savoir-faire naturalistes locaux : l’originalité française - Laurence Bérard; Marie Cegarra; Marcel Djama; Sélim Louafi; Philippe Marchenay; Bernard Roussel; François Verdeaux (VertigO, 2005)
Local ecological knowledge and know-how play a central role in the negotiations on the Convention on Biological Diversity. Here the authors present and analyze the specific characteristics of the French approach on the subject: the concepts of terroir and heritage, a reinterpretation of indigenousness, and diverse forms of conservation; all of these are often tied to enhancing the status of products via the market.